"n Postliberale perspektief op "n ekklesiologiese modaliteit as "n ecclesiola in ecclesia – heroriëntasie in die Nederduitsch Hervormde Kerk van Afrika - Aarde, Andries van (HTS teologiese studies, 2013)
A postliberal perspective on an ecclesiological modality as an ecclesiola in ecclesia – reorientation in the Netherdutch Reformed Church of Africa. This article investigates the legitimacy of a middle position between Reformed orthodoxy and critical theology. Is such a middle position the solution to the current conflict in the Netherdutch Reformed Church of Africa? The tension between ‘liberal’ and ‘orthodox’ is investigated by comparing these to the alleged tension between psychology and critical exegesis in Schleiermacher’s thinking. The article finds that these poles constituted a dialectic rather than a tension in Schleiermacher’s thinking. An organised middle group will lead to a greater schism in the Netherdutch Reformed Church. The argument unfolds by means of a reflection on 10 theological nuances, the most important of which are not the poles of conservative confessionalism and critical liberalism, but ethical-dialectical and critical-realistic theology. The conclusion is that reconciling diversity remains a Biblical-theological imperative rather than the organisation of an ecclesiological modality.